Urinary NGF, TGF-beta 1, TIMP-2 and Bladder Wall Thickness Predict Neurourological Findings in Children with Myelodysplasia - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; TARCAN, TUFAN (ELSEVIER SCIENCE INC, 2014)
Purpose: Dimercapto-succinic acid scintigraphy and urodynamic studies are gold standards to evaluate renal scarring and neurogenic bladder dysfunction, respectively. We sought to establish the value of bladder wall thickness together with urine NGF, TGF-beta 1 and TIMP-2 to predict the urodynamic profile and upper urinary tract damage in children with myelodysplasia. Materials and Methods: A total of 80 children with myelodysplasia underwent urodynamic investigation, bladder wall thickness measurement and dimercaptosuccinic acid scintigraphy with basic neurourological evaluation. Two study and 2 control groups were created according to presence or absence of renal scarring on dimercapto-succinic acid scan (study and control groups 1) and according to detrusor leak point pressure greater or less than 40 cm H2O (study and control groups 2). Urine samples were analyzed with ELISA. Results: The study population consisted of 44 girls and 36 boys with a median +/- SD age of 7.2 +/- 3.6 years (range 2 to 17). Study and control groups 1 consisted of 35 and 45 children with abnormal and normal dimercapto-succinic acid scan findings, respectively. Study and control groups 2 included 30 and 50 children with detrusor leak point pressure greater and less than 40 cm H2O, respectively. Bladder wall thickness and urinary levels of TGF-beta 1, NGF and TIMP-2 were significantly increased in both study groups compared to controls. Conclusions: Urine markers and bladder wall thickness measurement may predict urinary tract impairment in children with myelodysplasia. Such markers may differentiate at risk patients with either renal scarring or high detrusor leak point pressure, and decrease the need for urodynamics and renal scintigraphy.
Keywords: nerve growth factor; neural tube defects; tissue inhibitor of metalloproteinase-2; transforming growth factor beta1; urinary bladder; neurogenic; NERVE GROWTH-FACTOR; OVERACTIVE BLADDER; TRANSFORMING GROWTH-FACTOR-BETA-1; MATRIX METALLOPROTEINASES; ULTRASOUND ASSESSMENT; JUNCTION OBSTRUCTION; DETRUSOR THICKNESS; SMOOTH-MUSCLE; INHIBITORS